Uncovering the orbit of the hercules dwarf galaxy. Issue 2 (4th June 2020) - Gregory, Alexandra L; Collins, Michelle L M; Erkal, Denis; Tollerud, Erik; Delorme, Maxime; Hill, Lewis; Sand, David J; Strader, Jay; Willman, Beth
ABSTRACT: We present new chemo-kinematics of the Hercules dwarf galaxy based on Keck II-DEIMOS spectroscopy. Our 21 confirmed members, including 9 newly confirmed members, have a systemic velocity of v Herc = 46.4 ± 1.3 km s −1 and a velocity dispersion $σ _{v, Herc}=4.4^{+1.4}_{-1.2}$ km s −1, consistent with previous studies. From the strength of the Ca ii triplet, we obtain a metallicity of [Fe/H] = −2.48 ± 0.19 dex and dispersion of $σ _{\rm {[Fe/H]}}= 0.63^{+0.18}_{-0.13}$ dex. This result is within 1σ of previous measurements, and makes Hercules a particularly metal-poor galaxy, placing it slightly below the standard mass–metallicity relation. Previous photometric and spectroscopic evidence suggests that Hercules is tidally disrupting and may be on a highly radial orbit. From our identified members, we measure no significant velocity gradient. By cross-matching with the second Gaia data release, we determine an uncertainty-weighted mean proper motion of $μ _{α }^*=μ _{α }\cos (δ)=-0.153± {0.074}$ mas yr −1, μδ = −0.397 ± 0.063 mas yr −1 . This proper motion is slightly misaligned with the elongation of Hercules, in contrast to models which suggest that any tidal debris should be well aligned with the orbital path. Future observations may resolve this tension.